Using COHA to Explore the Usage of Accounting - Lu, Chunmei (Advances in Social Sciences Research Journal, 2018)
Accounting is a significant discipline in social science. This paper sets out to investigate the matching strings of accounting by examining a 400-million-word Corpus of Historical American English (COHA), enabling us to have better understanding about how accounting has gone through three processes and evolved into a discipline. The results show that 1) the frequency of accounting follows an upward but a little fluctuating trend from 1810s to 2000s; 2) in 1810s-1890s, accounting was in its infancy, the major searching results of COHA reveals a high frequency of the expression “accounting for”, which has little connection with a discipline; 3) in 1900s-1940s, the usage of accounting has become enriched, with a large number of diversified expressions like “the system of accounting, the accounting division, the accounting department, financial accounting” are quite common in COHA; 4) in 1950s-2000s, accounting has gradually been regarded as a discipline: students start to learn accounting lessons or major in accounting.